Medical Training in the United States Prior to the Civil War* - Robert G. Slawson MD, FACR (SAGE Publishing, 2012)
Early medical school development in the United States was considerably more robust than is usually appreciated. Most histories include only that portion of medicine known as regular or allopathic medicine. To fully understand developments in the country, it is necessary to include the various medical sects that developed in the country in the early 19th century. It is also important to realize that the impetus for medical school development came not from established academic institutions but from the medical community itself. Medical schools in the United States developed at a time and place that hospitals, as we know them, did not exist. The melding together of the preceptorship (apprenticeship), didactic lectures, demonstrations, and clinical/hospital experience evolved slowly. The move from heroic medicine occurred somewhat reluctantly as in Europe. In the United States, in contrast to the situation in Europe, the majority of medical practitioners were called "doctor." The development of medicine and medical education is usually discussed as a progression of knowledge. It has been fashionable to ignore the development of the various medical sects. Even within regular medicine, no uniformity of thought existed by this time. The American Medical Association was born of this. Change within a segment of society always reflects, and is reflected by, change in society at large. The rapid increases in geographic area and the huge population growth must be understood. Times changed as the character of the population changed. Perception of gender and freedom were important aspects of this change. A number of prominent African American physicians also emerged.